A retrospective analysis of vaginal birth after caesarian-predictors of success and its outcomes - Gautham, Kavitha; Thiruvengadam, Nalini; Viswanathan, Ramya; Jeeshia; Iyyer, Swarna Ganesan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: A repeat caesarian delivery (C-section) after a previous C-section increases maternal and foetal complication and poses an enormous burden on the economy of nations and individuals. The success of vaginal birth after C-section (VBAC) is affected by various antepartum, intrapartum factors as well as the difference in the obstetric population. This study aims to analyse the maternal and neonatal outcomes and factors associated with successful VBAC. Methods: The study is a retrospective analysis of 12 months hospital data conducted at BloomLife hospital, a private multispeciality hospital at Chennai during September 2022 to September 2023. The inclusion criteria were pregnant women with gestational age of 37±40 weeks who had intention for vaginal delivery, previous non recurrent indicating pregnancy, inter-delivery interval of at least 2 years, cephalic presentation, low risk pregnancies. High risk maternal and fetal factors were excluded from the study. Results: Among 204 women who had previous history of LSCS, 124 women were offered a trial of labour after caesarean (TOLAC) among which 56 (45%) of them successfully delivered through VBAC. Out of 124 women, 44 women out of 124, had opted for holistic approach during antenatal and intrapartum period among which n=27 (67.5%), had a statistically significant successful VBAC (Chi-square statistic is 6.25 p=0.012, significant at p<0.05). The most common reason for repeat C-section after TOLAC were labor dysfunction and fetal distress (n=2, 3.5%). Incidence of maternal complications in the study was atonic postpartum hemorrhage (n=7, 12.5%) that was well managed medically. All the babies had an Apgar >7 at 5 minutes. There was no maternal or neonatal mortality. Conclusions: Statistically significant rate of success was found in women who went into spontaneous labor and had antenatal and intrapartum holistic interventions. The study results demonstrates that an integrated approach with qualified birth support team will improve the success rate as well as reduce the maternal and fetal morbidity.